(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Duodenal ulcer, a type of peptic ulcer disease, is characterized by an open sore in the lining of the duodenum—the first part of the small intestine—primarily caused by excessive gastric acid secretion, Helicobacter pylori infection, or prolonged use of NSAIDs, leading to symptoms such as epigastric pain, acidity, and indigestion. This case study evaluates the integrative management of a 31-year-old male patient diagnosed with a duodenal ulcer, who presented to Jeena Sikho Lifecare Limited Hospital, Ambala, Haryana, India with chief complaints of gastritis and hyperacidity persisting for over five years. The patient had a history of alcohol consumption and exhibited elevated bilirubin levels upon initial evaluation. A holistic Ayurvedic treatment protocol was initiated, which included classical Ayurvedic formulations for their cooling and demulcent effects. A strict Pitta shamana diet was also advised. After Ayurvedic intervention, the patient reported significant symptomatic relief, including the resolution of gastritis and hyperacidity. Objective findings supported clinical improvement, with total bilirubin decreasing from 1.58 mg/dL to 0.98 mg/dL and corresponding improvements in direct and conjugated bilirubin levels, indicating better hepatic function. USG findings also demonstrated abdominal improvement. This case highlights the potential of Ayurvedic therapies in managing duodenal ulcers effectively. While results are promising, further large-scale and controlled studies are necessary to validate these outcomes and standardize treatment protocols.